Advanced Data Mining Tools and Methods for Social Computing. (6th April 2021) - Mohammed, Sabah; Fang, Wai Chi; Hassanien, Aboul Ella; Kim, Tai-hoon
Abstract: Social computing is a disruptive technology that is changing how we do business and building the enterprises. Mining consumer insights and consumer segmentation are the new drivers that are likely to be the cornerstone of developing new service innovations and social interactions. This special issue was designed to stimulate research on the data mining tools and methods for social computing. In this editorial, we are outlining the broad research framework on social computing, including the papers in this special issue and areas for future research .